Sexual maturation and fertility of mice exposed to triphenyltin during prepubertal and pubertal periods - Mello, Marcia Sarpa de Campos; Delgado, Isabella Fernandes; Favareto, Ana Paula Alves [UNESP]; Lopes, Camila M. T.; Batista, Marcelo Meuser; Kempinas, Wilma de Grava [UNESP]; Paumgartten, Francisco José Roma (Elsevier Ireland Ltd., 2015)
This study investigated the effects of pre- and peripubertal exposure (PND 15–45) to triphenyltin hydroxide (TPT: 0, 1.875, 3.75, 7.5 and 15 mg/kg bw/d po) on mouse sexual maturation and fertility. Half of the mice were euthanized on PND 46 and the remaining mice were submitted to fertility tests on PND 65–75. TPT caused a transient decrease of weight gain at 3.75 mg/kg bw/d, and deaths and body weight deficits at higher doses. Delays of testes descent (TD), vaginal opening (VO) and first estrus (FE) occurred at doses ≥3.75 (TD) and ≥7.5 mg/kg bw/d (VO, FE), respectively. Body weight on the days of TD, VO and FE did not differ among groups. TPT at doses ≥3.75 mg/kg decreased sperm and spermatid counts at the end of treatment (PND 46) but no alteration was noted later on PND 75. Testicular histopathology (PND 46) showed a dose-dependent reduction of seminiferous tubules diameter, a greater degree of vacuolation in Sertoli cells and germ cell degeneration and necrosis in TPT-treated mice. TPT did not affect the outcome of fertility tests. Study-derived NOAEL was 1.875 mg TPT/kg bw/d for males and 3.75 mg TPT/kg bw/d for females. The detrimental effects of TPT on spermatogenesis were reversed after treatment discontinuation.
Keywords: Triphenyltin; TPTH; Organotin compounds; Puberty; Postnatal exposure; Fertility